2018
DOI: 10.3389/fendo.2018.00408
|View full text |Cite
|
Sign up to set email alerts
|

Association of Nonalcoholic Fatty Liver Disease With Osteoporotic Fractures: A Cross-Sectional Retrospective Study of Chinese Individuals

Abstract: Objective: Nonalcoholic fatty liver disease (NAFLD) is related to several inflammatory or metabolic diseases. However, findings of previous studies investigating the association between NAFLD and BMD are inconsistent. Only one study reported a potential association between NAFLD and osteoporotic fracture. This study investigated whether NAFLD in older participants (>55 years) was associated with osteoporotic fracture risk.Materials and Methods: This cross-sectional, observational study included 2,695 participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 53 publications
6
36
1
Order By: Relevance
“…Moreover, it remains uncertain whether an association also exists between low BMD and severity of NAFLD. Recently, some large cross‐sectional studies of Chinese middle‐aged and elderly individuals also showed that ultrasound‐diagnosed NAFLD was significantly associated with a self‐reported history of osteoporotic fractures in older men, but not in women . Similar to observations in patients with obesity or type 2 diabetes, these latter findings raise the possibility that BMD might underestimate the long‐term risk of osteoporotic fractures in individuals with NAFLD (who are often obese or have diabetes).…”
Section: Introductionmentioning
confidence: 68%
See 4 more Smart Citations
“…Moreover, it remains uncertain whether an association also exists between low BMD and severity of NAFLD. Recently, some large cross‐sectional studies of Chinese middle‐aged and elderly individuals also showed that ultrasound‐diagnosed NAFLD was significantly associated with a self‐reported history of osteoporotic fractures in older men, but not in women . Similar to observations in patients with obesity or type 2 diabetes, these latter findings raise the possibility that BMD might underestimate the long‐term risk of osteoporotic fractures in individuals with NAFLD (who are often obese or have diabetes).…”
Section: Introductionmentioning
confidence: 68%
“…Figure summarises the results of the literature search and study selection. After excluding duplicates, based on titles and abstracts of 148 citations (in accordance with the aforementioned exclusion criteria of the meta‐analysis), we initially identified 17 potentially relevant studies from PubMed, Web of Science, and Scopus databases prior to 31 August 2018 (last date searched). After examining the full text of these 17 publications, we further excluded five studies, because of unsatisfactory inclusion criteria (ie, use of fatty liver index for diagnosing NAFLD or inclusion of patients with end‐stage liver disease awaiting liver transplantation) or unavailability of extractable data for BMD, as specified in the PRISMA flow diagram.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations